An anaerobic bacterium host system for heterologous expression of natural product biosynthetic gene clusters - Tingting Hao (Nature Portfolio, 2019)
Anaerobic bacteria represent a rich source of biological and chemical diversity but are difficult to cultivate and there is a lack of heterologous expression systems. Here the authors develop an expression system based on S. mutans UA159 for biosynthetic gene clusters from anaerobic bacteria.